The Impact of Community Belongingness on Mental Health and Well-Being Among Black LGBTQ Adults - Watts, Keith J. (Race and social problems, 2024)
The impact of racial and sexual minority stigma and discrimination on the mental health and well-being of Black and LGBTQ individuals, respectively, has been well documented in the literature. Research on these relationships for Black LGBTQ individuals who are multiply marginalized due to their position at the social intersections of gender identity, sexual orientation and race/ethnicity is less common. Belongingness to identity-based communities can protect against the negative impact of these minority stressors for Black and LGBTQ individuals and aid coping processes. However, Black LGBTQ individuals often experience stigma and discrimination in their racial, sexual, and gender minority communities due to their multiple minority identities. They may choose instead to create Black LGBTQ communities as a strategy to access the group- level coping resources needed to support their mental health and well-being in the face of compounded minority stress. Thus, the present study aimed to explore the relationships between identity-based community belongingness, coping, minority stress, mental health and well-being for Black LGBTQ individuals. Path and multiple regression analyses were conducted to test the hypothesized relationships between these variables in a sample (n = 345) of Black LGBTQ adults living in the United States. Study results found that: (1) community belongingness was associated with better mental health and well-being; (2) coping partially explained the relationships between community belongingness and well-being, but did not explain the relationship between community belongingness and mental health; (3) Black community belongingness was associated with better mental health; and (4) Black LGBTQ community belongingness was associated with better well-being. Implications for social work practice and education, and future research, are discussed.